Radicalization as martialization: towards a better appreciation for the progression to violence - Haggerty, Kevin D. (Terrorism and political violence, 2020)
The process whereby individual terrorists radicalize into violent extremism is typically understood as involving a series of individual mechanisms (e.g., grievance, attachment to friends, thrill), group processes (e.g., competition, social cohesion), and mass-public mechanisms. In this article, we demonstrate that this process is actually better understood as one of “martialization,” applicable to varying degrees to conventional and unconventional soldiers alike. We detail these commonalties via an analysis of six key themes in the literature: a) a sense of vicarious injustice, b) a sense of belonging/identity, c) meaning, excitement, and glory, d) active recruitment, e) indoctrination, and f) group solidarity. Lastly, we suggest why scholars have previously been blind to these parallels. By not recognizing the similarities, we are missing out on the opportunity to mobilize our entire existing knowledge base (on conventional and unconventional soldiers) for creating useful policies for countering violent extremism.